Eventum: A Journal of Medieval Arts and Rituals and its First Issue (Eventum: A Journal of Medieval Arts & Rituals, 2023)
This first introductory article presents the brand new, interdisciplinary, and diamond open access journal Eventum, along with the specific theme of Issue 1: “The Arts and Rituals of Pilgrimage”. It describes the rationale and scope of the journal in association with the three key terms of its subtitle, in reverse order: ‘rituals’, ‘arts’, and ‘medieval’. As for the topic of the present issue, which explores the arts and rituals of the medieval and postmedieval practice of pilgrimage, some important points are noted in relation to the issue’s five subsequent articles.
Keywords: introduction; eventum; first issue; journal for medieval arts and rituals; pilgrimage